PENGARUH PEMAHAMAN AKUNTANSI DAN SISTEM INFORMASI AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PADA PEMERINTAHAN KABUPATEN LEBAK - Taufiqurrohman Taufiqurrohman; Siti Mudawanah; Machmud Muthanudin (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2021)
This study aims to determine the effect of accounting understanding and accounting information systems on the quality of financial reports in Lebak regency government. This research uses quantitative methods. The type of data in this study is primary data. The study population was 13 OPDs (Regional Apparatus Organizations) in the Lebak Regency government, using the purposive sampling method. Where the sample used for each OPD was taken 6 people, namely the head of the department and employees / staff of the finance / accounting subdivision, who are technically involved in recording the financial transactions of the Work Unit and the preparation of government financial reporting as respondents totaling 78 samples / respondents. This study uses multiple linear regression analysis with the IBM SPSS Statistics 20 program. Based on the results of the study, it shows that accounting comprehension partially (X1) has a positive and significant effect on the quality of financial statements (Y), this is evidenced by the value of tcount ttable (2,680 1,994. ) and the significance is smaller than the probability value, namely 0.009 0.05. Partially the Accounting Information System (X2) has a positive and significant effect on the quality of financial statements (Y), this is evidenced by the value of tcount ttable (2.322 1.994) and the significance is smaller than the probability value, namely 0.023 0.05. And simultaneously Accounting Understanding (X1) and Accounting Information Systems (X2) have a significant effect together on the Quality of Financial Statements, this is evidenced by the value of fcount ftabel (9.400 3.14) and the significance is smaller than the probability value which is equal to 0.00 0.05.